OPEN JOURNAL SYSTEM SECURITY CAPABILITY LEVEL ASSESSMENT USING COBIT 5 FRAMEWORK AT ABDURRAB UNIVERSITY - M. Alfaraby; Megawati Megawati; Idria Maita; Fitriani Muttakin (Jurnal Teknik Informatika (Jutif), 2023)
Data security is very important in the digital era, this makes it an important issue for companies, organizations and educational institutions. Such as the Open Journal System (OJS) security which is useful for managing online journals. Abdurrab University has utilized the Open Journal System (OJS) to manage published journals. However, the management of the Open Journal System (OJS) security has not been managed properly, such as Abdurrab's Open Journal System (OJS) which has been hacked, there is still a lack of documentation and system security procedures and has never been assessed the level of capability of the information system so that it is not known exactly the level of security management of the Open Journal System (OJS) at Abdurrab University. This study aims to assess the capability level of Abdurrab University's Open Journal System (OJS) using the COBIT 5 domain DSS05 framework and Process Assessment Model (PAM) to assess system capabilities and guide IT management and provide effective and efficient recommendations. The results of the study obtained a questionnaire calculation value of 2.40 with Process Attribute Level domain DSS05 PA 2.1 Performance Management and PA 2.2 Work Product Management until an achievement score of 63.33% was obtained which was included in the Largely Achieved category with achievements at level 2 (Managed Process). The conclusion of this study is that the level of security capabilities of the Open Journal System (OJS) of Abdurrab University needs to be increased to level 3 (Established Process) because it has not been fully met, so that this research can be used as a reference for improvement by Abdurrab University.